Sanksi Pelaku Murtad dalam Perkawinan yang Masih Tinggal Bersama Perspektif Hukum Pidana Islam - Mubarok MR, Husni (Universitas Muhammadiyah Ponorogo, 2025)
Apostasy in Islam is considered a serious offense generally punishable by death. However, its application becomes complex when the apostate remains in a marital relationship, living with their spouse and children, thus raising legal dilemmas concerning family protection and the enforcement of sanctions under Islamic criminal law. This study aims to analyze the Islamic criminal law sanctions against apostates who continue to live with their families. Using a normative juridical method, the study examines the legal provisions from various sources, including the Qur’an, Hadith, and ijma’ (consensus of scholars). The findings reveal that the death penalty applies to apostates who leave Islam with the intention of opposing and destroying it. However, for individuals who apostatize but remain committed to protecting their family, the death penalty is deemed irrelevant. In such cases, a more prioritized approach involves counseling and efforts to bring them back to Islam. If these efforts fail, alternative sanctions such as ta’zir can be applied, including flogging, detention, fines, or reprimands, along with additional penalties such as asset freezing. In conclusion, under Islamic criminal law, apostates who maintain marital ties and live with their family are not subjected to the death penalty unless their apostasy is accompanied by hostility towards Islam and a desire to destroy it, as clarified in the historical development of Islamic law.